2010 IEEE International Conference on Ultra-Wideband 2010
DOI: 10.1109/icuwb.2010.5615732
|View full text |Cite
|
Sign up to set email alerts
|

UWB for in-body medical implants: A viable option

Abstract: Today's medical implants communicate with each other over radio, typically using standards such as MICS. However, in order to reduce power consumption and improve datarates, we need to explore better standards. Ultra wide band radios (UWB) are known to be low power. While studies on UWB radios for on-body implants exists, no study exists which explains the effect of UWB for in-body medical implants. This paper shows that Ultra wideband (UWB) can be a feasible solution for in-body medical implants in certain ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Moreover, it is recovered with a latex layer to avoid a short between the patch and the phantom. The in-body antenna was moved in steps of Δ Δy=Δ 1 cm x z   along X, Y and Z axis with a grid size of (Nx, Ny, Nz) = (12,11,2). Considering the fat layer to be the YZ plane and the center of the layer the reference position, the X axis moves closer or farther from the reference plane, the Y axis moves left or right and the Z axis moves up and down from the reference position.…”
Section: B Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is recovered with a latex layer to avoid a short between the patch and the phantom. The in-body antenna was moved in steps of Δ Δy=Δ 1 cm x z   along X, Y and Z axis with a grid size of (Nx, Ny, Nz) = (12,11,2). Considering the fat layer to be the YZ plane and the center of the layer the reference position, the X axis moves closer or farther from the reference plane, the Y axis moves left or right and the Z axis moves up and down from the reference position.…”
Section: B Methodologymentioning
confidence: 99%
“…As already mentioned, only the measurements with power above the noise level are computed. The path loss obtained can be modeled as a distance-dependent logarithmic function (2), where the shadowing term is given by N(µ,), a normal distribution with standard deviation  = 2.307 and zero mean…”
Section: A Experimental Path Loss Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 400 MHz band has been specially allocated for the implant to implant, implant to external and implant to body surface communications [3]. In several research papers the UWB band has also been suggested [18][19][20]. Narrowband 13.5, 50, 400, 600, 900 MHz and 2.4 GHz bands are suggested for body surface communications between non-implanted sensors.…”
Section: Body Area Networkmentioning
confidence: 99%
“…In the case of WBAN, this band was initially envisioned for wearables (on-body) devices [12]. Nonetheless, its multiple advantages, such as low power consumption and antenna miniaturization, have led it to be considered as a good candidate for in-body high data rate communications [24]- [27]. For example, cortical implants [27], and novel wireless capsule endoscope [28], have been addressed in the literature to benefit from this technology.…”
Section: Uwb Propagation Environment For Medicalmentioning
confidence: 99%